CONFIRMATORY FACTOR ANALYSIS INTERNAL DAN EKSTERNAL KEUANGAN, FREE CASH FLOW, DAN RETURN SAHAM PERUSAHAAN MANUFAKTUR GO PUBLIC DI INDONESIA - Widi Hidayat (EKUITAS (Jurnal Ekonomi dan Keuangan), 2009)
The negative impact of economic crisis in Asia to internal financial decision included investment decision, financing decision, and dividend decisions. This condition is loser if external factors such as  inflation rate, interest rate, and exchange rate are not supported. Negative free cash flow including Economic Value Added and Market Value Added, depreciation of stock return indicate financial distress and reduction of shareholder wealth.The research used of Confirmatory Factor Analysis and the hypotheses are: The influence of Inflation Rate (IR), Interest Rate, and Exchange Rate are significant to External Factor.The influence of Return on Equity (ROE), Fixed Asset Utilization (FAU), Capital Intensiveness (CI), Inventory Intensiveness (II), Receivable Intensiveness (RI), Margin Ratio (MR), Asset Profitability Ratio (APR) are  significant to Investment Decision.The influence of Financial Leverage (FL), Short Term Liquidity (STL) and Cash Position (CP) are  significant to Financing Decision.The influence of Plowback Ratio (PR) and Return On Fixed Asset are  significant to Dividend Decision.The influence of Economic Value Added (EVA) and Market Value Added (MVA) are significant to Free cash flow.The influence of Price Earning Ratio (PER), Dividend Yield (DY), and Capital Gain Yield (Cap.G) are  significant to Stock Return.The results of this research are significant influence to external factors, internal financial decision, free cash flow, and stock return;  but inventory and receivable intensiveness, dividend yield are not significantly.